Qualitative Study On The Perception Of Third-Trimester Pregnant Women With Anemia Regarding Compliance With Fe Tablet Consumption - R. Heris Mulyawati Purnama Dewi Kusumah; Yulia Herliani; Santi Yuliastuti (Poltekkes Kemenkes Tasikmalaya, 2026)
Background : Anemia in pregnancy has a negative impact on both the mother and the fetus, making adherence to iron tablet consumption a crucial part of anemia prevention programs. The perceptions of pregnant women in their third trimester influence adherence to iron tablet consumption, with positive perceptions increasing adherence, while side effects, lack of knowledge, and low awareness become barriers. Objectives : This study aimed to determine the perceptions of anemic pregnant women in their third trimester regarding adherence to iron tablet consumption in the Tawang Community Health Center (Puskesmas), Tasikmalaya City. Methods : The study used a qualitative approach through in-depth interviews with six pregnant women, with supporting informants including health cadres, husbands, and parents. Result : showed that knowledge, consumption experience, support from family and health workers, and maternal motivation played important roles in improving adherence to iron tablet consumption. Conclusion : That some pregnant women are compliant in consuming Fe tablets.